2017
DOI: 10.1186/s13104-017-2581-1
|View full text |Cite
|
Sign up to set email alerts
|

Very low sensitivity of wet mount microscopy compared to PCR against culture in the diagnosis of vaginal trichomoniasis in Uganda: a cross sectional study

Abstract: Background Trichomonas vaginalis (TV) causes the Trichomoniasis Syndrome composed of vaginitis in women, urethritis in men and tube infection in both sexes. This infection is strongly associated with premature rupture of membranes, preterm delivery, low birth weight, promoting HIV sexual transmission and infertility. Prevention of these complications requires accurate early detection and effective treatment of infected individuals. In the resource limited settings, the wet mount microscopy (WMM) is often the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…The prevalence of T. vaginalis in women differs in different populations, where it is ten times higher than men. The infection comprises the risks of premature delivery birth, low birth weight, infertility, and cervical cancer (6,7). Clinical manifestations of the parasite are different in men and women.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of T. vaginalis in women differs in different populations, where it is ten times higher than men. The infection comprises the risks of premature delivery birth, low birth weight, infertility, and cervical cancer (6,7). Clinical manifestations of the parasite are different in men and women.…”
Section: Introductionmentioning
confidence: 99%
“…Although a study from Aligarh[ 19 ] reported similar positivity rate by acridine orange staining, nonetheless, they could detect only 66% positive cases by wet mount microscopy as in a study from Karnataka[ 20 ] with a resultant lower sensitivity (60%). Studies from Uganda (25%)[ 21 ] and Egypt (33.3%)[ 22 ] have even lower sensitivity of wet mount microscopy. A delay in transport of the sample with resultant reduced motility of the organism can compromise with sensitivity of this technique.…”
Section: Discussionmentioning
confidence: 99%
“…Among the T. vaginalispositive women, a decrease was observed in the sensitivity of the WMM, compromising treatment of two-thirds of the patients. The authors recommend further research to integrate PCR tools into diagnostic algorithms for trichomoniasis [25].…”
Section: Wet Mountmentioning
confidence: 99%